PENGARUH PERKEMBANGAN EKONOMI DIGITAL TERHADAP DAYA SAING UMKM DI INDONESIA - Hasan Rahman Nasution; Maryam Batubara (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to analyze the impact of digital economic development on the competitiveness of micro, small, and medium enterprises in Indonesia. The focus of the study includes identifying supporting and inhibiting factors in digital economic development that affect the competitiveness of micro, small, and medium enterprises, as well as providing practical policy recommendations for the government and related parties. The research method used is a literature review, which synthesizes findings from scientific journals, government reports, and related research to provide an in-depth overview of this topic, as well as to explore research gaps related to the specific influence of the digital economy on the competitiveness of micro, small, and medium enterprises in Indonesia. The results of the study show that the digital economy provides great opportunities for micro, small, and medium enterprises, such as wider market access, increased operational efficiency, and export capabilities, but faces major challenges such as the digital divide, high technology costs, and a lack of digital literacy. The main supporting factors include the Proudly Made in Indonesia National Movement program, while inhibiting factors such as difficulties in accessing technology and capital remain major obstacles. The study concludes that although the digital economy has great potential, the challenges faced by micro, small, and medium enterprises require the active role of the government in optimizing digitization policies and reducing the digital divide. Practical policy recommendations include digital training, technology incentives, and increased access to capital to support micro, small, and medium enterprises in adapting to the digital economy.   Keywords: Digital Economy, MSME Competitiveness, Digital Transformation, Indonesia, Policy Recommendations   Abstrak: Penelitian ini bertujuan untuk menganalisis dan membandingkan sistem zakat di Qatar dan Indonesia dari aspek regulasi, kelembagaan, mekanisme pengelolaan, dan efektivitas distribusinya terhadap kesejahteraan masyarakat. Qatar sebagai negara berpendapatan tinggi dengan sistem zakat yang terintegrasi dalam kebijakan sosial negara, menunjukkan model filantropi Islam yang didukung penuh oleh pemerintah dan lembaga resmi seperti Ministry of Awqaf and Islamic Affairs serta Qatar Charity. Sementara itu, Indonesia menerapkan sistem zakat dengan dualisme kelembagaan melalui Badan Amil Zakat Nasional (BAZNAS) dan Lembaga Amil Zakat (LAZ) yang berperan penting dalam memberdayakan masyarakat miskin. Metode penelitian ini bersifat kualitatif deskriptif dengan pendekatan komparatif, menggunakan sumber data sekunder dari laporan resmi lembaga zakat, jurnal akademik, dan peraturan perundang-undangan. Hasil penelitian menunjukkan bahwa sistem zakat di Qatar lebih terpusat dan terintegrasi dengan kebijakan negara, sementara di Indonesia lebih partisipatif dan berbasis masyarakat. Namun, tingkat efektivitas penyaluran zakat di Indonesia masih menghadapi tantangan dalam aspek transparansi, digitalisasi, dan pemerataan distribusi. Kajian ini merekomendasikan sinergi antara model Qatar yang terpusat dan model Indonesia yang berbasis partisipatif untuk menciptakan sistem zakat yang lebih adaptif dan inklusif di era ekonomi modern.   Kata Kunci: Ekonomi Digital, Daya Saing UMKM, Transformasi Digital Ekonomi, Indonesia, Rekomendasi Kebijakan